Can't be far : poems - Myers, Jed, 1952- (MoonPath Press, 2026)
"In his poetry collection Can't Be Far, Jed Myers writes with masterfully restrained music and luminous imagery as he questions how to survive the losses and griefs that haunt us all-the aging body, the deaths of family and friends, and a world of tyranny and violence so distorted by "the makers of our new facts" that we barely recognize it. Guiding us through the dark, Myers, who claims to be "Late // for my remedial lessons in gentle," helps us "untie beauty // from horror" in this "muffled chorus" of "hundreds on hundreds / of hunkered souls," while paving the way toward "love's presence," and therefore love's courage, that surely Can't Be Far" -- Amazon.com